Issues and images – new sources of inequality in current representative democracy. Issue 3 (3rd May 2016) - Thaa, Winfried
Abstract : Right from its beginning, representative democracy was criticized for promoting inequality. Nonetheless, for many decades representative democracy has led to more equality – politically as well as socially. Meanwhile, in most Western societies this has dramatically changed. Trying to understand this change, the paper will first identify the immanent egalitarian tendencies in modern democratic representation. I will argue that not only universal franchise, but, paradoxically, also the distinction between society and the stage of political representation have had strong egalitarian effects. I will continue to demonstrate that the development from party to audience democracy together with the rise of non-electoral modes of participation transformed the performative and configurative functions of political representation. Instead of translating social conflicts into reasonably consistent political alternatives, parties try to identify strategically promising issues in order to create attractive media images. Together with the growing weight of issue-oriented, non-electoral participatory activities, this development threatens to undermine the political realm as a distinct sphere of equals.